THE IMPLICATION OF ASSERTIVE UTTERANCE FOR PERSONALITY DEVELOPMENT AND LANGUAGE USE - Tiara Resta Putri; Sutarman; Agus Syahid; Titik Ceriyani Miswaty; Syamsurrijal (Jurnal Bastra (Bahasa dan Sastra), 2025)
The phenomenon of speech act is functions as a tool for communication and a reflection of one’s thoughts, beliefs, and personality. This study aims to analyze assertive speech acts used by the main character, Moana, in the animated musical film Moana 2, and how those speech acts reveal the development of her personality. This study applied descriptive qualitative method with data collection technique through documentation and analysis of Moana’s utterances in the movie. A total of 176 utterances identified based from Moana and only 69 of them were categorized as assertive speech acts. The findings show forms of assertive utterance include stating, claiming, suggesting, reporting, boasting, admitting, and concluding. This research also contributes to the field of linguistics, especially in connecting speech act (Searle, 1969) with Big Five Personality Traits and enriching the understanding of how language reflects personality growth. These forms of speech acts reflect Moana’s change from an informative figure to an individual who is more confident, reflective, and has a great love for new things.  Thus, this study not only provides an overview of various assertive speech acts but also bridges the gap between pragmatic theory and personality.